The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ldr.3809
|View full text |Cite
|
Sign up to set email alerts
|

Erosion at hillslope and micro‐basin scales in the Gilbués desertification region, Northeastern Brazil

Abstract: With an area of 6,200 km2, the Gilbués badlands region in the Brazilian drylands is the largest desertification site in the Country. It is located upstream the Boa Esperança Hydroelectric Power Plant and is contiguous to an important Brazilian agricultural area. However, primary quantitative data on erosive processes are scarce or nonexistent. We analyzed on‐site data (2018–2019) concerning small‐scale (hillslope and micro basin) processes: inter‐rill gross erosion, vegetation coverage factor, sediment yield, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 59 publications
4
10
0
Order By: Relevance
“…The efficiency of the model for total siltation rate is 0.96 (Table 6), its classification ranges from very good (Moriasi et al, 2007) to good (Ritter and Muñoz-Carpena, 2013). It supports the argument that stationary parameters such as relief (in our temporal analysis scale) play a relevant role for sediment delivery mechanisms (Simplício et al, 2020); they, therefore, increase the performance of the model over time.…”
Section: Sediment Yield Modellingsupporting
confidence: 75%
See 4 more Smart Citations
“…The efficiency of the model for total siltation rate is 0.96 (Table 6), its classification ranges from very good (Moriasi et al, 2007) to good (Ritter and Muñoz-Carpena, 2013). It supports the argument that stationary parameters such as relief (in our temporal analysis scale) play a relevant role for sediment delivery mechanisms (Simplício et al, 2020); they, therefore, increase the performance of the model over time.…”
Section: Sediment Yield Modellingsupporting
confidence: 75%
“…Gaiser et al (2003) found that, for the Brazilian northeast region, the most fit among those equations is the one by Maner Maner (1958, hereafter Equation 10). Simplício et al (2020) had the same result for the dry Cerrado region of Gilbués (Fig. 2).…”
Section: Gross Erosion and Siltation Assessmentsupporting
confidence: 67%
See 3 more Smart Citations